Identification and Pathogenicity of Cladosporium Musae Mason from Banana Leaf Speckle - Sahlan (2003)
A study was undertaken to isolate and identify Cladosporium sp. from banana leaves associated with a speckle disease which is considered a serious problem especially in 'Berangan' and 'Mas' cultivars planted in Teluk Intan, Perak 0/Vest Malaysia). Direct plating of infected 'Berangan' banana leaves surface sterilized in 5% sodium hypochlorite (NaOCI) solution on Potato Dextrose Agar (PDA) failed to isolate Cladosporium sp. However, pure cultures were successfully obtained by a single spore isolation method. Conidia from diseased leaves were first scrapped using a fine paint brush into sterile water. The conidial suspension was then poured over 2% water agar 0/VA) incorporated with antibiotics (streptomycin and tetracycline sulphate) and incubated for 24 hours at ambient temperature. A single germinated conidia was picked with an inoculation needle and transferred onto a PDA plate similarly a mended with antibiotics. The fungus produced erect conidiophores and conidia which were mainly fusiform and aseptate or 1-septate on banana leaves. Conidiophores on Malt Extract Agar (MEA) were straight and flexuous, and produced conidia and ramoconidia which were very variable in shape and size. A comparison between the morphological characteristics and dimensions of the Teluk Intan fungus on banana leaves and culture medium with those previously described in literature suggest its close similarity and synonymous identification with Cladosporium musae Mason. The best culture medium for growth of C. musae Mason was on Banana Leaf Extract Agar (BLEA), while MEA and PDA were the best culture medium for supporting maximum conidia production. In culture, it can grow between a temperature range of 18°C to 30°C, but the optimum temperatures for mycelial growth and sporulation were 22°C and 26°c respectively. The optimum temperature for conidial germination was 26°C combined with relative humidity (RH) of between 99% to 100%.